Influence of Regional Tectonics on The Geological Formations of The Locality of Mabuku in Beni Territory - Deogratias Anguandia Odhipio; Maombi Kalimuli Kakule (MO.RI Publishing, 2022)
The locality of Mabuku is located in the eastern DRC, in a landscape where tectonic effects are visible. The main cause of this environmental disturbance is known as tectonics. This study aims to determine the influence of regional tectonics (like Kibalian, Ruzizian and Kibarian tectonics) on rocks of the locality of Mabuku, and their types. After the fieldwork and the data processing, we got the following results: firstly, none filled faults were due to constraints of the compressive type, which are also similar to those affecting the formations of the group of Ruzizi. Secondly, the schistosity of these rocks was due to extensive type stresses and its direction is similar to Kibarian tectonics. Moreover, the veins were generated by a constraint of the compressive type, bounding them to Kibalian tectonics. In conclusion, in the locality of Mabuku there’s a combination of the Ruzizian, Kibalian, and Kibarian tectonics.